School‐based fluoride varnish programs: a national survey. (3rd September 2019) - Bakhurji, Eman; Hoaglin Cooper, LeeAnn
Abstract: Purpose: To identify and describe school‐based fluoride varnish (FV) programs in K‐12 grades children in the United States. Methods: This cross‐sectional study utilized an online, self‐administered survey to identify and describe school‐based FV programs in 2016. Several public health directories, mainly The Association of States and Territorial Dental Directors directory, were contacted to identify FV programs. The survey's questionnaire included 23 closed‐ended questions regarding program description, assessment, and process. Results: Of 85 identified programs, 52 responded (response rate = 61 percent) with 40 school‐based FV programs in operation in 27 states. About 85 percent of responding programs apply FV as part of an existing school‐based program. Dental sealants on permanent teeth are the most common procedure provided in addition to FV (92 percent). One‐third of programs apply FV once a year versus 28 percent that apply FV twice a year. Conclusions: Evidence‐based guidelines for FV in school‐based programs are needed to ensure cost‐effectiveness and continuity.